Epidemiology of Penile Fracture in Local Population - Al.Mufti, Mohammed Suhaib; Muhammed, Mazen Yones (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and Objectives: Penile fracture has been reported with sexual intercourse, masturbation, rolling over or falling on to the erect penis. Patients and Methods: between August 2005 to August 2009 we prospectively prepare 21 patients with diagnosis of ’fractured’ penis. Recording details age, time of attendance, cause, symptoms, signs, site of rupture, operative findings, and final outcome. Results: A total of 21 patients were identified. The mean age was 29 years (range, 22-49 years). The interval between time of injury and presentation ranged from 50 minutes to 8 days. Ten (48%) cases were attributed to sexual intercourse, 6 (28%) to penile manipulation, 2 (10%) to rolling over the erect penis during sleep, and 3(14%) falling on to the erect penis. Nineteen patients underwent surgery; all had primary suturing of the tunica tear, while two also required primary urethral repair. At follow-up, 3 patients had erectile dysfunction, 3 had mild penile deformity and one had a mild urethral stricture. Conclusions: early surgical repair ensure a successful outcome with minimal complications. The public should be educated about that condition to seek medical attention immediately, as delay may result in permanent complication that could be avoided.